Computer spirometry: Research of respiratory system functionality and its enhancement in young swimmers - Zakharova, A.; Gorelov, A.; Miasnikova, T. (Proceedings of the 8th International Conference on Sport Sciences Research and Technology Support, 2020)
The control of the swimmers' fitness should include an assessment the respiratory system. The aim of the study to evaluate the age features of respiratory system in young swimmers and suggest the methods for respiratory system improvement. Methods: young athletes underwent two tests with MicroLab spirometry; relaxed and forced vital capacity measurement. Findings: (i) young swimmers 10-11 years old with at least 5 years of experience in swimming showed low spirometry indicators (85% of predicted value); (ii) the more experienced and successful swimmers the better their respiratory system developed. High-performance sport swimmers have high level (120 % of predicted value) of all spirometry indicators; (iii) breathing exercises selected for solving the respiratory problems in swimmers improve the respiratory muscles functionality.